Cocaine self-administration behaviors in ClockΔ19 mice - Ozburn, Angela Renee (2012)
RATIONALE: A key role has been identified for the circadian locomotor output cycles kaput (Clock) gene in the regulation of drug reward. Mice bearing a dominant negative mutation in the Clock gene (ClockΔ19 mice) exhibit increased cocaine-induced conditioned place preference, reduced anxiety- and depression-like behavior, increased sensitivity to intracranial self-stimulation, and increased do-paminergic cell activity in the ventral tegmental area. OBJECTIVES: We sought to determine if this hyperhedonic phenotype extends to cocaine self-administration and measures of motivation. METHODS: Two separate serial testing procedures were carried out (n=7–10/genotype/schedule). Testing began with acquisition of sucrose pellet self-administration, implantation of intravenous catheter, acquisition of cocaine self-administration, and dose–response testing (fixed ratio or progressive ratio). To evaluate diurnal variations in acquisition behavior, these sessions occurred at Zeitgeber 2 (ZT2) or ZT14. RESULTS: WT and ClockΔ19 mice exhibited similar learning and readily acquired food self-administration at both ZT2 and ZT14. However, only ClockΔ19 mice acquired cocaine self-administration at ZT2. A greater percentage of ClockΔ19 mice reached acquisition criteria at ZT2 and ZT14. ClockΔ19 mice self-administered more cocaine than WT mice. Using fixed ratio and progressive ratio schedules of reinforcement dose–response paradigms, we found that cocaine is a more efficacious reinforcer in ClockΔ19 mice than in WT mice. CONCLUSION: Our results demonstrate that the Clock gene plays an important role in cocaine reinforcement and that decreased CLOCK function increases vulnerability for cocaine use.